2001
DOI: 10.1210/endo.142.12.8650
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Expression of the Human Vitamin D Receptor to the Keratinocytes of Vitamin D Receptor Null Mice Prevents Alopecia

Abstract: Vitamin D receptor (VDR) null mice develop hypocalcemia, hyperparathyroidism, rickets, osteomalacia and alopecia. Normalization of mineral ion homeostasis prevents all of these abnormalities except alopecia. Hair reconstitution assays, performed in athymic nude mice, demonstrate that the lack of VDR in keratinocytes leads to a defect in anagen initiation, similar to that observed in VDR null mice. Although these studies demonstrate that expression of the VDR in keratinocytes is necessary, they do not prove tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…Chen et al [20] and Kong et al [21] have shown that specific expression of WT VDR in keratinocytes of VDR knockout mice can restore hair growth. Skorija et al [22] have recently shown that keratinocyte-targeted expression of either a mutant VDR (L233S) that does not bind ligand or a mutant VDR (L417S) that is defective in binding coactivators can restore hair growth in VDR knockout mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [20] and Kong et al [21] have shown that specific expression of WT VDR in keratinocytes of VDR knockout mice can restore hair growth. Skorija et al [22] have recently shown that keratinocyte-targeted expression of either a mutant VDR (L233S) that does not bind ligand or a mutant VDR (L417S) that is defective in binding coactivators can restore hair growth in VDR knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…VDR knockout mice, generated by disrupting exon 2 [18] or exon 3 [19] that constitute the DBD, also exhibit alopecia. Hair growth can be restored by specific expression of WT VDR in keratinocytes of VDR knockout mice [20,21]. Importantly, keratinocyte-targeted expression of transactivation defective mutant VDRs with mutations that affect ligand binding or that prevent coactivator binding also restored hair growth [22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, hair cycling is greatly affected in VDR knockout animals (14,15) and in many patients with hereditary hypocalcemic vitamin D-resistant rickets type II (HVDRR-II), (16) although this process is not compromised in vitamin D deficiency. In addition, the secondary bile acid, lithocholate, has been recently recognized as a bona fide VDR ligand in the colon, capable of activating VDR to induce detoxifying, cytochrome P450-containing enzymes.…”
Section: A S Shown Inmentioning
confidence: 99%
“…(17) The VDR is also absolutely required for a functional hair cycle as exemplified by the known phenotype of alopecia in HVDDR-II patients (16) and in VDR knockout mice. (14,15) Furthermore, essential polyunsaturated fatty acid (PUFA) deficiency has adverse effects on skin, including impaired hair growth and dermatitis. (55)(56)(57)(58) Administration of PUFAs such as linoleic acid has been shown to reverse these symptoms.…”
Section: Molecular Action Of Vdr Ligands V7mentioning
confidence: 99%
“…It has been reported that vitamin D plays an important role in cutaneous immune modulation [7][8][9]. The active form of vitamin D (1,25-dihydroxyvitamin D) acts as an immunomodulator targeting various immune cells such as macrophages, monocytes, dendritic cells as well as T lymphocytes and B lymphocytes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%